The mother-daughter book club : a novel [compact disc, unabridged] - Patterson, Susan, 1957-; Patterson, James, 1947- (Blackstone Publishing, 2026)
Between their busy lives and their far-flung residences, the Mother-Daughter Book Club--four longtime college friends and their five daughters--more often discuss the books on their nightstands via 2 a.m. texts than at in-person meetings. So it's an emotional reunion when they finally gather again, this time on the spectacular shores of Italy's Lake Como. These friends, and sometime rivals, are close readers of novels, memoirs, and each other. But as the years and the distance cast shadows and doubt, confidences and sympathies turn into surprising revelations.